2014
DOI: 10.1111/bpa.12220
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Multiple Sclerosis: Clinical, Radiologic and Pathologic Insights

Abstract: Cognitive impairment is a common and debilitating feature of multiple sclerosis (MS) that has only recent gained considerable attention. Clinical neuropsychological studies have made apparent the multifaceted nature of cognitive troubles often encountered in MS and continue to broaden our understanding of its complexity. Radiographic studies have started to decipher the neuroanatomic substrate of MS-related cognitive impairment and have shed light onto its pathogenesis. Where radiographic studies have been lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 211 publications
(335 reference statements)
5
113
1
4
Order By: Relevance
“…This is an efficiency model rather than a threshold model, and it implies that the task can be processed using fewer resources and in a manner that makes errors unlikely to occur. Cognitive reserve declines with MS disease progression (Sumowski and Leavitt, 2013;DeLuca et al, 2015). Functional MRI studies obtained from PwMS during cognitive tasks have consistently shown a more widely distributed cortical recruitment than in healthy …”
Section: Discussionmentioning
confidence: 99%
“…This is an efficiency model rather than a threshold model, and it implies that the task can be processed using fewer resources and in a manner that makes errors unlikely to occur. Cognitive reserve declines with MS disease progression (Sumowski and Leavitt, 2013;DeLuca et al, 2015). Functional MRI studies obtained from PwMS during cognitive tasks have consistently shown a more widely distributed cortical recruitment than in healthy …”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment causes substantial individual disease burden and socioeconomic costs as it is a major contributor to poor vocational status and premature retirement in people with MS. [19][20][21] Moreover, it has a significant negative impact on health-related quality of life 22 and may impede the success of rehabilitation. 19 Although the literature on the association between cognitive dysfunction and fatigue is conflicting, the high prevalence of both (up to 90% of MS patients reporting fatigue [23][24][25][26] ) will result in concomitant occurrence of both fatigue and cognitive impairment in a substantial proportion of patients which does not necessarily imply causality.…”
mentioning
confidence: 99%
“…Between 40% and 70% of patients with MS are affected by cognitive impairments [5], which are linked to a significant decline in activities of daily living. Despite the rapidly growing amount of research establishing frequent social cognitive deficits in such patients, there is still no statistics on the frequency of this type of disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairments in MS are heterogeneous [2] and their rate varies between 43% and 70% [3][4][5]. They are in an independent form of disability and make the performance of routine daily activities difficult, sometimes impossible.…”
Section: Introductionmentioning
confidence: 99%